2002
DOI: 10.1348/135910702169349
|View full text |Cite
|
Sign up to set email alerts
|

An exposure‐based examination of the effects of written emotional disclosure

Abstract: OBJECTIVES: We undertook this study to clarify the operative mechanisms that account for the relationship between emotional disclosure and health. We hypothesized that emotional disclosure via writing was a form of exposure-based therapy and that exposure was the active therapeutic component. Design and method. A group of 129 male and female undergraduates were randomly assigned to three writing groups: (1) a trauma disclosure writing group; (2) a positive emotion writing group to control for affect arousal; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 20 publications
2
59
3
1
Order By: Relevance
“…Repetition of each writing session decreases distress experienced while writing and leaves individuals feeling less emotional after each writing session, both in positive and negative affect. These findings contrast with Kloss and Lisman (2002) who argued that negative affect does not decrease over the course of each writing session. Differences between this study and that of Kloss and Lisman include the use of a measure of distress while writing, as opposed to after writing, and the request that participants focus on one upsetting event in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…Repetition of each writing session decreases distress experienced while writing and leaves individuals feeling less emotional after each writing session, both in positive and negative affect. These findings contrast with Kloss and Lisman (2002) who argued that negative affect does not decrease over the course of each writing session. Differences between this study and that of Kloss and Lisman include the use of a measure of distress while writing, as opposed to after writing, and the request that participants focus on one upsetting event in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…First, the sample examined in this study consisted of college students who were not preselected on the basis of psychologic or physical health problems. Although similar samples have been frequently used to study the written disclosure procedure (5,6,9,12,29,31), the results obtained with this type of sample may not generalize to the general population. Additionally, as previously noted, the use of a college student sample may have influenced the findings with regard to gender.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of empirical attention to gender differences and written disclosure, in response to Smyth's meta-analysis results, a number of investigators have speculated that the written disclosure procedure might be particularly beneficial for men because it provides an anonymous context for men to disclose feelings of distress and vulnerability (5)(6)(7)(8)(9). Strengthening this tentative hypothesis for why men might derive particular benefits from written disclosure is the finding that relative to men, women typically report that their relationships are characterized by greater intimacy, emotional disclosure, and empathy (10).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of inconsistent findings in student, community, and clinical populations, however, have raised concerns about the effectiveness of unstructured writing (e.g., Gidron, Peri, Connolly, & Shalev, 1996;Greenberg & Stone, 1992;Greenberg, Wortman, & Stone, 1996;Kloss & Lisman, 2002;Rosenberg et al, 2002;Stroebe, Stroebe, Schut, Zech, & van den Bout, 2002). A recent meta-analysis of 146 research trials using various unstructured emotion writing methods concluded that the impact of this type of writing approach may have some benefits for some individuals, but the overall effect size was very small (effect size ¼ 0.075; Frattaroli, 2006).…”
Section: Introductionmentioning
confidence: 99%